Changes in glycosylated proteins in colostrum and mature milk and their implication - Lu, Jing; Zhang, Wenyuan; Ma, Changlu; Pang, Xiaoyang; Dai, Ying; Zhu, Tong; Liu, Jinqi; Xing, Lina; Zhang, Shuwen; Lv, Jiaping (Frontiers in Nutrition, 2023)
Glycosylation is one of the essential post-translational modifications that influences the function of milk proteins. In the present study, 998 proteins and 764 glycosylated sites from 402 glycoproteins were identified in human milk by TMT labeling proteomics. Compared to human milk proteins, the glycoproteins were mainly enriched in cell adhesion, proteolysis and defense/immune process. The abundance of 353 glycosylated sites and their 179 parent proteins was quantified. After normalization to their parent protein's abundance, 78 glycosylated sites in 56 glycoproteins and 10 glycosylated sites in 10 glycoproteins were significantly higher in colostrum and mature milk, respectively. These changed glycoproteins were mainly related to host defense. Intriguingly, one glycosylated site (Asp144) in IgA and two glycosylated sites (Asp38 and Asp1079) in Tenascin are significantly upregulated even though their protein abundance was downregulated during lactation. This study helps us figure out the critical glycosylated sites in proteins that might influence their biological function in an unbiased way.